Brazil [videorecording (DVD)] (2014)
Be astounded by the fifth largest country in the world, from the lost world of Amazonia, to the buzzing cities of Rio de Janeiro and Sao Paolo, a city of 30 million, where the super rich commute by helicopter. Meet remote tribes who pit their survival skills against gold diggers and loggers. In the entertaining company of good-natured host Michael Palin, delight in the spectacular landscape, food, music, beach life and unique cultural heritage of a rising global power.